Anti-sperm antibodies in homosexual men: prevalence and correlation with sexual behaviour. Issue 1 (February 1990) - Mulhall, B P; Fieldhouse, S; Clark, S; Carter, L; Harrison, L; Donovan, B; Short, R V
Abstract : The sera of 60 homosexual males were examined for the presence of antibodies to sperm using an indirect immunobead test (IBT). Six of 60 (10%) had antibodies of IgG isotype; in addition two of the six had antibodies of IgA isotype. The presence of antibodies was associated with the practice of unprotected receptive anal intercourse in the previous six months. Antibodies were not found in homosexual men who were celibate, or who practised only oral intercourse during the same period. There was no correlation between the presence of anti-sperm antibodies and antibodies to human immunodeficiency virus (HIV), or numbers of T lymphocytes. These preliminary results lend support to the hypothesis that antigen presentation in the lower gut may be a source of sensitisation against sperm. The possibility that anti-sperm antibodies may be a marker of receptive anal intercourse merits further investigation.